Altitudinal and Seasonal Effect on Herbaceous Biomass in Tehsil Takht-E-Nasrati, District Karak, Pakistan (Global Journal of Science Frontier Research, 2012)
To record the existing herbaceous biomass diversity of Tehsil Takht-e-Nasrati, Pakistan, field surveys were regularly conducted in spring, summer and winter 2009-2010. There was an increasing inclination of Biomass as of spring to winter. However, the collective amount of grasses and herbs Biomass (426.5 Kg.hec-1) was significantly higher during spring at Stand 1 as compared to other seasons and Stands. The average grasses and herbs Biomass was decreasing with increasing altitude. The herb Biomass was high (730 Kg.hec-1) during spring at Stand 1 and low during summer (194 Kg.hec-1) at Stand 4. The grass Biomass was high during summer (173 Kg.hec-1) at Stand 3 and less during winter (74 Kg.hec-1) at Stand 1. The total herb mean Biomass was greater during spring (536.30 Kg.hec-1) while the grass had (129.9 Kg.hec-1) during summer. The total average Biomass was high at Stand 1 (262.58 Kg.hec-1). The total mean and average Biomass of Tehsil Takht-e-Nasrati was 223.23 Kg.hec-1. The Biomass of herbs helps to conserve the bio energy, chemical constituents and heat in existing area.
Keywords: herbaceous biomass; seasonal effect; altitudinal effect; Takht-e-Nasrati; pakistan